A gestão estratégica dos canais de distribuição: um exame da evolução e do atual estágio do relacionamento entre o atacado de entrega e a indústria - Alcântara, Rosane Lúcia Chicarelli (1997)
The skill to management reIationship in the marketing channels is today a detenninant eompetitive faetor. The distributors must be seen as an strategie partner, linked to the manufaetures through information systems, in order to establish a new relationship where the traditional adversary way of doing business eould be ehanged by an integrative approaeh. As long as this relationship offers attraetives business opportunities, there is a laek of understanding about the aetual stage of this process and its evolution. This misu nderstanding diffieulties strategies formulations that could improve this practiee whieh inerease the ehannel members results and the service leveI to the customers. The objective of this dissertation was to examine the present stage of the relationship between wholesalers and manufaeturers, trying to verify the evolution and the factors that ean faeilitate and eonstrain this processo The unit of analysis was the wholesalers and their suppliers in the groeely industry. The developed approaehes of this proeess, their faeilitated and eonstrained characteristies, the partner request, the operationaI and strategic changes and the signs of their evolution are presented as the main results.